2014
DOI: 10.1515/med-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged paradoxical reaction to antituberculous treatment after discontinuation of TNF-alpha- blocker therapy with adalimumab. Rare clinical documentation

Abstract: AbstractIn the past decades, tumor necrosis factor alpha (TNF-a) antagonist has been a milestone in the treatment of many chronic inflammatory diseases. TNF antagonist can increase patients´ susceptibility to many different kinds of infections especially those requiring granuloma formations despite regular performance of Screening for latent tuberculosis infection (LTBI). We report 2 cases of patients who developed tuberculosis under treatment with adalimumab, which was discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To our knowledge, besides our case, 28 cases of a PR in miliary tuberculosis in non-HIV-infected patients have been reported in the past 40 years (Table 1) [[7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]]. The manifestations described depended on the site of involvement.…”
Section: Discussionmentioning
confidence: 62%
“…To our knowledge, besides our case, 28 cases of a PR in miliary tuberculosis in non-HIV-infected patients have been reported in the past 40 years (Table 1) [[7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]]. The manifestations described depended on the site of involvement.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study showed that patients undergoing therapy with TNF-α-blockers are prone to develop TB infection. 33 Previous studies have shown that excessive TNF-α levels cause damage to the immune pathological response in cells and to protection of the body’s defense. 34 36 TNF-α levels may be related to the severity of the disease process and may serve as a parameter for predicting the prognosis of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…It may seem paradoxical to treat TB-IRIS with TNF-I, given the known role of TNF-alpha in controlling mycobacterial infection [9]. However, several studies have shown that paradoxical reactions to antituberculosis treatment occur when TNF-I treatment is stopped [10][11][12]. Bana et al [6] showed that TNF-I discontinuation can lead to extended IRIS, particularly in cases of TB involving the lymph nodes.…”
mentioning
confidence: 99%